The impact of economic fluctuations on earnings forecast - Ata Molodpoor; Roya Darabi (Management Science Letters)
Previous studies in the area of earnings forecasts hold a common characteristic, they make no distinction as to the economic cycle when evaluating voluntary earnings disclosures. This paper presents an empirical investigation to study the relationship between actual as well as forecasted earnings and growth domestic product during the economic growth and recession on Tehran Stock Exchange. Using the information of 60 firms over the period of 2007-2012, the study has determined that there was a positive and meaningful relationship between earnings forecast and growth domestic product during economic growth. In addition, the study has determined a meaningful relationship between actual earnings and growth domestic product during the recession.